Height and diameter of nocturnal perches selected by juveniles and adults of common chameleon (Chamaeleo chamaeleon). - Farfán-Aguilar, Miguel Ángel; Duarte, Jesús; Romero-Pacheco, David; Colorado-Pedrero, Laura; García-Quevedo, Pablo; Díaz-Ruiz, Francisco (Universidad de Málaga, 2024)
Cannibalism by adults of conspecific juveniles has been reported in wild populations of common chameleon (Chamaeleo chamaeleon). In view of this cannibalistic behaviour by adults, we hypothesise that juvenile chameleons should select nocturnal perches with distinct characteristics from those chosen by adults, thus avoiding them. To test this hypothesis, we examined nocturnal perch selection by adults and juveniles over seven months of field monitoring of a chameleon population in southern Iberia. Our results support the hypothesis of cannibalism as a selective force leading to differential habitat use by juveniles and adults because juveniles select unstable perches that are inaccessible to adults and avoid spatial overlap with adults, including sharing the same plant foot. The database is structured in six fields describing the following information about each common chameleon found: date, type of plant, branch diameter (mm) and height (cm) on which the individual was found, weight (g) and age (juvenile/adult).
Keywords: Camaleones - Hábitos y conducta; Canibalismo en animales; Camaleones - Hábitat; Common chameleon; Nocturnal perch selection